Conceptual and methodological issues relevant to cytokine and inflammatory marker measurements in clinical research - Zhou, Xin; Fragala, Maren S; McElhaney, Janet E; Kuchel, George A (Current opinion in clinical nutrition and metabolic care, 2010)
To provide clinical investigators with an understanding of factors to consider when wishing to add cytokine and inflammatory marker measurements to their studies. Inflammation involves complex and coordinated responses of the immune system to tissue damage. In the absence of tools to routinely assess inflammation within living tissues, measurements of humoral factors such as cytokines and other inflammatory mediators or markers can provide predictive clinical information and insights into disease mechanisms. Historically, enzyme-linked immunosorbent assays (ELISAs) became the gold standard, yet this approach of measuring a single protein in each sample limits the amount of information which can be obtained from limited amounts of human sample. In recent years, commercially available multiplex technologies which detect large numbers of proteins in a limited volume have provided investigators with opportunities to begin addressing the complexity of inflammatory responses. Nevertheless, great attention needs to be paid to many aspects of study design, sample collection, sample measurement and data analysis. These considerations are especially significant when using technologies for which experience remains limited. Whereas measurements of peripheral levels of inflammatory markers can add important mechanistic elements to human subject research, careful attention to conceptual and methodological considerations is essential, especially when using novel technologies.